Autoimmune Thyroid Diseases and Helicobacter Pylori - Vincenzo Bassi; Olimpia Fattoruso; Crescenzo Santinelli (Open Journal of Thyroid Research - Peertechz Publications, 2017)
Background: Helicobacter pylori infection is worldwide diffused with up to 50% of incidence in the population of the developed countries and the most virulent strains carrying the cytotoxin-associated gene A antigens. Moreover, bacterial and viral antigens have been suspected to be able to mimic the antigenic profile of the thyroid cell membrane suggesting an important role in the onset of the autoimmune diseases, such as Graves' disease and Hashimoto's thyroiditis. Aims: we reviewed the studies concerning the relationship between the bacterium and the autoimmune thyroid diseases such as Graves' and Hashimoto's disease. Conclusions: the significative association between Helicobacter pylori and Graves' disease suggests a possible role of this bacterium in the onset and/or the maintenance of the autoimmune disease.